The impact of antenatal Bisphenol A exposure on male reproductive function at 20–22 years of age - Hart, R.; Doherty, D.; Keelan, J.; Minaee, Noviani; Thorstensen, E.; Dickinson, J.; Pennell, C.; Newnham, J.; McLachlan, R.; Norman, R.; Handelsman, D. (Elsevier Ltd, 2018)
© 2017 Bisphenol A (BPA) is a ubiquitous chemical suspected to possess oestrogenic hormonal activities. Male population studies suggest a negative impact on testicular function. As Sertoli cell proliferation occurs during fetal or early postnatal life, it is speculated that oestrogenic environmental exposures may influence mature testicular function. Among 705 Western Australian Pregnancy Cohort (Raine) Study men aged 20–22 years, 404 underwent testicular ultrasound examination (149 had maternal serum available), and/or 365 provided semen (136 had maternal serum) and/or 609 serum samples for sex steroids, gonadotrophins and inhibin B analysis (244 had maternal serum). Maternal serum collected at 18 and 34 weeks' gestation was pooled and assayed for concentrations of total BPA (free plus conjugated) as an estimate of antenatal exposure. Testicular volume was calculated by ultrasonography, and semen analysis performed. Serum LH, FSH and inhibin B were measured by immunoassay; testosterone, oestradiol, oestrone andBPA were measured by liquid chromatography-mass spectrometry. BPA levels were detectable in most (89%) maternal serum samples. After adjustment for maternal smoking, abstinence and varicocele, sperm concentration and motility were significantly correlated to maternal serum BPA (r = 0.18; P = 0.04 for both). No other associations of maternal serum BPA with testicular function were observed.